2011
DOI: 10.1007/s12072-011-9255-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of serum HBV DNA load on recurrence of hepatocellular carcinoma after treatment with percutaneous radiofrequency ablation

Abstract: Serum HBV DNA load is associated with the risk of recurrence of HBV-related HCC after RFA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 35 publications
(36 reference statements)
1
22
0
Order By: Relevance
“…The rate of HCC recurrence and mortality at 2 years after RFA in the present study was similar to those found in previous studies (54.8% vs 42.3 ~ 60.9% and 16.2% vs 16.2%) . Tumor multiplicity, liver cirrhosis, platelet count, and LS value were the independent predictors of HCC recurrence.…”
Section: Discussionsupporting
confidence: 90%
“…The rate of HCC recurrence and mortality at 2 years after RFA in the present study was similar to those found in previous studies (54.8% vs 42.3 ~ 60.9% and 16.2% vs 16.2%) . Tumor multiplicity, liver cirrhosis, platelet count, and LS value were the independent predictors of HCC recurrence.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, Goto et al . reported that serum HBV DNA load (>10 4 copies/mL) was associated with tumor recurrence in HBV‐related HCC after radiofrequency ablation in a retrospective study with 69 patients . In contrast, several studies found that the presence of high viral load did not affect the HCC recurrence after ablation .…”
Section: Discussionmentioning
confidence: 95%
“…We also removed one report since its interest was HBV DNA titer in surrounding liver. Finally, a total of 17 articles [1, 1922, 2637] were pooled into analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretically, HCC recurrence may partly be attributable to metachronous multicentric carcinogenesis and de novo HCC [18], which could be enhanced by HBV load. Some of previous studies [19, 20] showed that high viral load (HBV DNA levels > 10 5 copies/ml) promotes the recurrence of HCC, but this significant associations were not estimated by Chung et al [21] and Mathews et al [22]. Considering the controversial results which have been yielded by previous studies, and the limited power which was estimated by the studies with relatively small sample size, the obscure relationship between HBV load and recurrence of HCC was urgent to be clarified by a meta-analysis with enough power via combining the basis of published data.…”
Section: Introductionmentioning
confidence: 99%